Intellectual emptiness and its relationship to mental distraction among some students of the College of Physical Education and Sports Sciences - Meriam Abdul-ameer; Dr. Sahira Razzaq (الرياضة المعاصرة)
The study aimed to prepare psychological measures of intellectual emptiness and mental distraction on university students. The two researchers used the descriptive approach in the two methods of surveying and correlational relations to suit the nature of the research, where the study sample consisted of (101) students of physical education and sports sciences.  The phrase- Intellectual emptiness(35) and (34) is a phrase for mental distraction and presented it to experts in psychology, testing and measurement, and the statistical bag for social sciences (spss) was used, and the results of the research showed that intellectual emptiness has a moral relationship with straying among some students of the College of Physical Education and Sports Sciences, and the necessity  Providing a university environment dominated by an atmosphere of intellectual openness and respect for opinion and the other opinion